Adsorption of Methylene Blue by Bentonite Supported Nano Zero Valent Iron (B-nZVI) - Zarime N.?.; Solemon B.; Wan Yaacob W.Z.; Jamil H.; Che Omar R.; Rafek A.G.; Roslan R. (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Dyes used in textiles, foods, cosmetics, and chemicals have become a major environmental pollution issue around the world. To address this issue, a number of technologies have been created to remove these pollutants from the environment. Due to their superior properties at nanoscale, numerous nanomaterials have been applied to remove dyes from polluted waters. This research presents the findings of the development of bentonite nano zero-valent iron (B-nZVI) for the treatment of synthetic cationic dyes. This study has three objectives: (i) to produce bentonite nano zero-valence iron (B-nZVI), (ii) to characterize its adsorbents (B-nZVI), (iii) to characterize its adsorption capacity. Four main tests were used for this purpose: (i) a physical test (BrunauerEmmettTeller (BET) surface area), (ii) a chemical test (cation exchange capacity (CEC) and X-ray fluorescence (XRF)), (iii) morphology (field emission scanning electron microscopy (FESEM) and (iv) mineralogy (Fourier transform infrared spectroscopy (FTIR). The five factors for the batch equilibrium test are adsorbent dose, concentration, kinetic, pH, and temperature. The batch test showed that the optimum dose for all adsorbents is 0.5 g. For the concentration factor, B-nZVI exhibits larger adsorption capacity (KL = 30,314.0536 L/g